'Free and Equal Partners in Your Commonwealth': The Atlantic Charter and Anticolonial Delegations to London, 1941–3. (10th August 2017) - Reeves, Mark
Abstract: This article examines the efforts of two anticolonial politicians from the British Empire who used official visits to London and the rhetoric of the Atlantic Charter (14 August 1941) to advance their political careers and self-government for their territories: Burma's U Saw in 1941, and Nigeria's Nnamdi Azikiwe in 1943. Rather than a repetition of the 'Wilsonian moment', these campaigns show how anticolonial forces long active across the Empire took advantage of the opening offered by the Atlantic Charter to make claims on the British government in its wartime weakness. Both U Saw and Azikiwe had been involved in anticolonial politics long before the Charter, but its appearance provided an opportunity to advance their position vis-à-vis political competitors as well as to win concessions from the imperial state. Although the two leaders had different immediate objectives, they both used the prestige of official visits to London and the ambiguous universality of the Charter's language in pursuit of their aims. Their ability to do so attests to the power of anticolonial movements by the early 1940s, and points to alternative paths which the Empire might have followed.